PERFORMANCE MANAGEMENT EVALUATION IN IMPROVING WORK MOTIVATION AT THE HILISALAWA'AHE DISTRICT OFFICE SOUTH NIAS REGENCY - Serta Bahagia Halawa; Odaligoziduhu Halawa; Eliagus Telaumbanua; Fatolosa Hulu (Jurnal Ilmiah METADATA, 2026)
The purpose of this study is to analyze how performance management evaluation can contribute to improving employee work motivation in government. The research method used is a qualitative approach, with data collection techniques using interviews, observation, and documentation. The results of the study indicate that performance management evaluation at the Hilisalawa'ahe District Office is conducted routinely based on indicators set out in the Work Plan (Renja) and Minimum Service Standards (SPM). Factors influencing employee work motivation include clarity of objectives, a fair reward system, and effective communication between superiors and subordinates. Regarding performance evaluation, various obstacles were found, such as the lack of a formal and transparent reward system, and minimal constructive feedback for employees. This study recommends the need to develop a more structured reward system and implement Key Performance Indicators (KPI) based indicators to improve the objectivity of performance assessment at the Hilisalawa'ahe District Office.